The Colonial Sugar Industry in Indonesia and the Philippines: A Comparative Perspective - Nawiyanto Nawiyanto; Jose Wendell Capili; Nina Mutiara Calvaryni (Paramita: Historical Studies Journal, 2023)
The sugar industry played a significant role in the colonial economies of Indonesia and the Philippines. Growing the same commodity for the global market, the conditions under which the sugar industry operated in the two places were quite different. Using historical methods and drawing upon secondary sources, this article compares the colonial sugar industry in Indonesia with particular reference to Java and the Philippines between 1890 and 1940. Unlike the case of Indonesia, where the sugar industry operated in densely populated lowland areas, the Philippine sugar industry was established in a sparsely populated region. However, the sugar producers in the two countries took various measures to make their ventures more efficient and competitive. This article will outline broadly the early development of the sugar industry in Java and the Philippines, followed by a discussion on the choice of production technology and the performance of the sugar industry in the interwar period to provide a better understanding of the different development of the sugar industry in Java and the Philippines. The sugar industry in Java was more successful in improving its productivity and efficiency, making the industry more competitive than the Philippines. However, the sugar industry in the two countries had different destinies when the global crises hit hard in the 1930s. Only because of the preferential treatment obtained in the American market did the less efficient sugar industry in the Philippines survive during the Depression. Meanwhile, Java's more efficient sugar industry collapsed due to the unfair protection policy in the world sugar market.Industri gula memainkan peran penting dalam perekonomian kolonial di Indonesia dan Filipina. Menumbuhkan komoditas yang sama untuk pasar global, kondisi industri gula yang beroperasi di kedua tempat tersebut cukup berbeda. Dengan menggunakan metode sejarah dan memanfaatkan sumber-sumber sekunder, artikel ini membandingkan industri gula kolonial di Indonesia dengan referensi khusus di Jawa dan Filipina antara tahun 1890 dan 1940. Berbeda dengan kasus di Indonesia, dimana industri gula beroperasi di daerah dataran rendah yang padat penduduknya, Filipina industri gula didirikan di wilayah yang jarang penduduknya. Namun, produsen gula di kedua negara mengambil berbagai langkah untuk menjadikan usaha mereka lebih efisien dan kompetitif. Artikel ini akan menguraikan secara garis besar perkembangan awal industri gula di Jawa dan Filipina, dilanjutkan dengan diskusi mengenai pilihan teknologi produksi dan kinerja industri gula pada periode antar perang untuk memberikan pemahaman yang lebih baik mengenai perbedaan perkembangan industri gula di Jawa dan Filipina. industri gula di Jawa dan Filipina. Industri gula di Pulau Jawa lebih berhasil meningkatkan produktivitas dan efisiensinya, sehingga industri ini lebih kompetitif dibandingkan Filipina. Namun industri gula di kedua negara mempunyai nasib yang berbeda ketika krisis global melanda pada tahun 1930an. Hanya karena perlakuan istimewa yang diperoleh di pasar Amerika, industri gula yang kurang efisien di Filipina dapat bertahan selama masa Depresi. Sementara itu, industri gula di Jawa yang lebih efisien terpuruk akibat kebijakan proteksi yang tidak adil di pasar gula dunia.